New COI records of Myripristis kuntee (Pisces: Holocentridae) from Indonesia and preliminary genetic comparison with Asian public sequences - NADYA TIRTA; ESSY HARNELLY; RANIA FERANITA FACHRI; PUTRI KHAIRANI AMALIA SIREGAR; NANDA MUHAMMAD RAZI; NANDA ULFA KHAIRA; MUTIA RAMADHANIATY; SRI RISKA RAHAYU; NURLITA PUTRI ANGGRAINI; RAISSHA AMANDA SIREGAR; ADRIAN DAMORA; NUR FADLI (Society for Indonesian Biodiversity, 2026)
Abstract. Tirta N, Harnelly E, Fachri RF, Siregar PKA, Razi NM, Khaira NU, Ramadhaniaty M, Rahayu SR, Anggraini NP, Siregar RA, Damora A, Fadli N. 2026. New COI records of Myripristis kuntee (Pisces: Holocentridae) from Indonesia and preliminary genetic comparison with Asian public sequences. Biodiversitas 27 (5): d270530. https://doi.org/10.13057/biodiv/d270530. Shoulderbar soldierfish (Myripristis kuntee) is a reef-associated fish of ecological and economic importance widely distributed across the Indo-Pacific. However, molecular data for this species in Indonesian waters remain limited. This study provides the first cytochrome c oxidase subunit I (COI) based genetic record of M. kuntee from Indonesia and provides a preliminary genetic comparison with publicly available Asian sequences. Five specimens were collected in July 2024 from fishermen at a fish landing site in Ujung Pancu, Aceh Besar, Indonesia. A total of 27 mitochondrial COI sequences were analyzed, including five newly generated samples and 22 sequences retrieved from GenBank (Philippines, China, Taiwan, Bangladesh, and India). Sequence alignment and phylogenetic analyses were performed using MEGA, haplotype analyses were conducted in DnaSP, and genetic diversity indices were calculated using ARLEQUIN. Fifteen haplotypes were identified across six populations. The Philippines exhibited high haplotype diversity (Hd = 0.924; π = 0.025), while Indonesia showed moderate haplotype diversity (Hd = 0.700; π = 0.002), and Bangladesh exhibited no detectable variation. Genetic distances ranged from 0.002 between Indonesia and China to 0.219 between the Philippines and Bangladesh, suggesting close affinity between Indonesian and Chinese sequences but substantial mitochondrial divergence among some regional samples. Phylogenetic analysis revealed two clusters: China, the Philippines, Indonesia, and Taiwan grouped together, suggesting a close mitochondrial relationship, whereas Bangladesh clustered with one Indian sequence. These findings establish baseline COI barcode data for M. kuntee from Indonesia and provide preliminary insights into regional mitochondrial variation, although broader and more balanced sampling is required to confirm these patterns.